The Value of Normal Sleep in Iceland: An Empirical Analysis - Eva Rós Birgisdóttir 1997- (2020)
The costs associated with inadequate sleep have been estimated in various ways. However, the private utility losses associated with inadequate sleep have not been estimated. In this study, the relationship between happiness and sleep characteristics is analyzed. Using the compensating income variation (CIV) method, a monetary value is placed on sub-optimal sleep using individual-level panel data from the Directorate of Health in Icelandic, a health-and-lifestyle survey carried out in 2007, 2009, 2012, and 2017. To better understand the impact of sleep, results are stratified by gender. Various model specifications are used to gauge the importance of possible biases due to covariates, anxiety and depression, that are known to be associated with sleep and shift work that naturally affects sleep. Similarly, biases due to endogeneity of income are addressed. Results show that the willingness to pay (WTP) for transitioning from too little sleep to the recommended 7-9 hours average sleep length is positive, for both men and women. The CIV estimates, adjusted for income endogeneity, are $53,858 per year for females and $66,911 per year for males. Men generally have higher CIV values, which appears to be mostly driven by the male’s lower marginal value of income, rather than a greater marginal value of sleep improvements. The aggregated costs associated with utility reductions due to insufficient sleep in Iceland are estimated at $3.8 billion, corresponding to 15.2% of Iceland´s 2017 GDP. In comparison to previous researches on the economic burden of insufficient sleep, the costs of utility losses due to insufficient sleep are found to be substantial.